Silencing the critics: understanding the effects of cocaine sensitization on dorsolateral and ventral striatum in the context of an Actor/Critic model - Takahashi, Yuji; Schoenbaum, Geoffrey; Niv, Yael (Frontiers in Neuroscience, 2008)
A critical problem in daily decision making is how to choose actions now in order to bring about rewards later. Indeed, many of our actions have long-term consequences, and it is important to not be myopic in balancing the pros and cons of different options, but rather to take into account both immediate and delayed consequences of actions. Failures to do so may be manifest as persistent, maladaptive decision-making, one example of which is addiction where behavior seems to be driven by the immediate positive experiences with drugs, despite the delayed adverse consequences. A recent study by Takahashi et al. (2007) investigated the effects of cocaine sensitization on decision making in rats and showed that drug use resulted in altered representations in the ventral striatum and the dorsolateral striatum, areas that have been implicated in the neural instantiation of a computational solution to optimal long-term actions selection called the Actor/Critic framework. In this Focus article we discuss their results and offer a computational interpretation in terms of drug-induced impairments in the Critic. We first survey the different lines of evidence linking the subparts of the striatum to the Actor/Critic framework, and then suggest two possible scenarios of breakdown that are suggested by Takahashi et al’s data. As both are compatible with the current data, we discuss their different predictions and how these could be empirically tested in order to further elucidate (and hopefully inch towards curing) the neural basis of drug addiction.